BIO-MASTIC (Mastitis Natural Antiseptic), Pemanfaatan Ekstrak Daun Kersen sebagai Antiseptik Tear Dipping - Oktavia, Vinna; Umam, Ahmad Azmi Khoirul; Purwaningsih, Ratu Tintin; NofitaSari, Anissa; Ramadani, Nurul Qamaril (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
"BIO-MASTIC" is based natural antiseptic compounds containing antibacterial protection cherry leaves. thing more support in making this antiseptic is a special antiseptic product innovation Teat Dipping that has never existed in the market, another advantage with natural ingredients that have been tested, so as to provide protection of live stock against the disease through treatment mastitis post-milking TeatDipping. This productis more economical prices so that farmers do not spend a lotto take care of their animals. "BIO-MASTIC" has great potential to be developed areas such as dairy cattle centers in poor districts and Kota batu and can earn big profit. The Progress of programs divided into six stages including market research and planning, the purchase of means of production, the search for raw materials, implementing production, testing and marketing of products. Stage of market research conducted in the central areas of the dairy farm, the method used is to interview farmers to dairy farmers. Production Stage conducted in the Laboratory of FKM(Microtechnic Physiology and Plant Tissue Culture, the amount of production for 4 months obtained 248 liters. Stage product testing carried out in the laboratory of FKM (Physiology, Plant Tissue culture and Microtechnic) Faculty of Biology and Bacteriology laboratory Brawijaya University. at the marketing stage, we aim at a target market that is central areas of the dairy farm. Mean while applied marketing strategy is to go to the breeder directly and in cooperation with Prosperous UD.Sumber. Moreover, we follow the bazaars both campus and national levels. "BIO-MASTIC" business innovation antiseptict eat dipping first in Indonesia in the field of prospective and sustainable farms, so as to address the needs of animals in an effort to overcome the problems of lack of antiseptics for milking. hoped would also createa goodbrand image and product support antiseptic"BIO- MASTIC", so it has the potential to be commercialized in Indonesia.Keywords : Mastitis, Natural Protection, Teat Dipping, profitable, sustainable.